2011
DOI: 10.1007/s10803-011-1414-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Data in a Sample of Greek Children with Autism Spectrum Disorders

Abstract: The purpose of this study is to describe clinical and laboratory data, as well as comorbid disorders in Greek children with autism spectrum disorders (ASD). Data were retrospectively collected for 222 children aged 1.5-9 years. The mean age at diagnosis was 43.7 ± 17.6 months. Significantly earlier diagnoses were noted in children with comorbid disorders (epilepsy, hearing deficits, genetic/metabolic disorders), mental retardation and a large head circumference (HC). Macrocephaly (HC ≥ 97th percentile) was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 37 publications
2
20
0
3
Order By: Relevance
“…Converging evidence from magnetic resonance imaging and HC studies has documented that individuals with ASD have larger brains and heads than comparison subjects (3,616,4043). HC has been shown to be a good measure of brain volume in children less than 6 years of age, with high correlation (0.96) between both measures at this age (44,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Converging evidence from magnetic resonance imaging and HC studies has documented that individuals with ASD have larger brains and heads than comparison subjects (3,616,4043). HC has been shown to be a good measure of brain volume in children less than 6 years of age, with high correlation (0.96) between both measures at this age (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…HC studies typically report increased rates (11~27%) of macrocephaly (HC≥97 th percentile or 2 standard deviations) in ASD compared with general population (616). However, some studies suggested that the use of national normative samples as control data could introduce biases including ancestry and secular effect (1719).…”
mentioning
confidence: 99%
“…7 Fewer than 5% of ASD cases are attributable to inherited metabolic disorders for which screening is routine, such as phenylketonuria. 3,8 The observation of autistic symptoms in patients with creatine deficiency syndromes (CDSs) implies that impairment in creatine metabolism may play a role in the neurobiology of ASD and if so it may represent a treatable cause of ASD. 9 The prevalence of CDS in children with ASD is unknown.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Table 1 lists the 34 studies identified by our systematic review(1522,24,25,35,4466), according to publication date and study characteristics.…”
Section: Findings: Systematic Reviewmentioning
confidence: 99%